2016
DOI: 10.3390/su8101044
|View full text |Cite
|
Sign up to set email alerts
|

Municipal Solid Waste Characterization According to Different Income Levels: A Case Study

Abstract: Solid waste generation and characterization are some of the most important parameters which affect environmental sustainability. Municipal solid waste (MSW) characterization depends on social structure and income levels. This study aims to determine the variations in waste components within MSW mass by income levels and seasonal conditions following the analysis conducted on the characterization of solid wastes produced in the Kartal district of the province of Istanbul, which is the research area of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(76 citation statements)
references
References 22 publications
5
61
1
9
Order By: Relevance
“…The daily waste collection was 621 kg/day, which indicates an average generation of 0.50 kg/capita/day. PCG in Morelia is below the values reported in other studies for cities in countries such as Cyprus [7], Turkey [6] or Oman [30] whose MSW generation rates range from 0.97 to 1.29 kg. However, it is bigger than Ghana [31] or China [32].…”
Section: Domestic Solid Waste Characterisationcontrasting
confidence: 70%
See 2 more Smart Citations
“…The daily waste collection was 621 kg/day, which indicates an average generation of 0.50 kg/capita/day. PCG in Morelia is below the values reported in other studies for cities in countries such as Cyprus [7], Turkey [6] or Oman [30] whose MSW generation rates range from 0.97 to 1.29 kg. However, it is bigger than Ghana [31] or China [32].…”
Section: Domestic Solid Waste Characterisationcontrasting
confidence: 70%
“…The percentages do not follow a particular pattern according to GDP. Food scrap in this study was comparable to the rates of countries with a lower GDP [37], and was smaller than countries with a higher GDP [6]. Authors [30,38] have found that waste composition varies according to the season of the year, the lifestyles of the generators, demography, and geographic zones, among others.…”
Section: Domestic Solid Waste Characterisationsupporting
confidence: 55%
See 1 more Smart Citation
“…Awareness and information of the wider public on the subject is crucial for the waste management field, as about 57% of total waste production is organic, with their highest percentages found amongst low income regions [25]. This kind of organic household management would be very suitable and valuable in farms, especially if initiative was taken to implement this case study on a larger scale.…”
Section: Resultsmentioning
confidence: 99%
“…Increased solid waste amount pose difficulty in efficient waste management process (transportation, storage and disposal) [10]. Worldwide quantity and composition of solid waste varies with region/state, climate and socio-economic conditions [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%